Evolution of Volatile Flavour Compounds during Fermentation of African Oil Bean (Pentaclethra macrophylla Benth) Seeds for “Ugba” Production - C. O. Nwokeleme; J. Obeta Ugwuanyi (International Journal of Food Science)
Fermented African oil bean (Pentaclethra macrophylla Benth) seed is a successful and well studied seasoning and snack in parts of Western Africa. GC-MS analysis of fermenting seeds revealed a mixture of several volatile aroma compounds which changed with time and starter organism. During natural mixed culture process 36 volatile compounds including 12 hydrocarbons, 10 esters, 5 alcohols, 2 phenols, 2 ketones, and one each of furan, amine, acid, thiophene, and lactone were identified. When Bacillus subtilis was used in pure culture, 30 compounds comprising 10 hydrocarbons, 8 esters, 3 alcohols, 2 amines, 2 sulfur compounds, and one of each of acid, aldehyde, phenol, ketone, and furan were identified. Sample fermented with B. megaterium produced 29 aroma compounds comprising 9 hydrocarbons, 10 esters, 2 nitrogenous compounds, 2 ketones, 3 alcohols, and one of each of lactone, aldehyde, furan, and amine. Methyl esters of various long chain fatty acids may be key aroma compounds, based on consistency and persistence. Qualitative or quantitative contribution of individual compounds may only be determined following flavour threshold analysis.